A 3-D finite element analysis of the effect of dental implant thread angle on stress distribution in the surrounding bone - Katayoun Sadr; Seyyed Mahdi Vahid Pakdel (Tabriz University of Medical Sciences, 2022)
Background. This study aimed to evaluate the effect of an increase in fixture thread face angle on the amount and distribution of stresses in the surrounding bone of implants with four different thread shapes by three-dimensional finite element analysis. Methods. Eight different fixture designs, with v-shaped, buttress, reverse buttress, and trapezoid threads, and two face angles of 20 and 35 degrees, were modeled using a software program. Each model was affected by two static forces with different values and angles (200-N axial 0° force and 100-N 45° oblique force) to compare the distribution of stress in different fixture designs. Results. The maximum von Mises stress was detected in v-shaped threads. An increase in the angle of the threads to 35° significantly decreased maximum von Mises stress in cortical bone in v-shaped and reverse buttress threads; however, the von Mises stress in the trapezoid and buttress threads increased with an increase in the thread angle. Conclusion. Under the limitations of this study, although the shape of the thread and thread surface angle does not have a definite role in stress distribution in the bone surrounding the implant, they are effective in the amount and type of stress induced in the bone supporting the implant.